2009
DOI: 10.1088/0953-8984/21/47/474208
|View full text |Cite
|
Sign up to set email alerts
|

Using surface and interface optics to probe the capping, with amorphous Si, of Au atom chains grown on vicinal Si(111)

Abstract: The distinct optical signatures of aligned single and double Au atom chain structures, grown on vicinal Si(111) substrates, have been identified using reflectance anisotropy spectroscopy (RAS). Deposition of 0.04 monolayers (ML) of amorphous Si (a-Si) at room temperature perturbs the anisotropic optical response of the double chain structure. By one third of a monolayer, no significant optical anisotropy associated with the chains remains. No anisotropic response re-emerges at higher coverages, up to 4.6 nm (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It has been shown previously, for the anisotropic systems, that the RAS response is very sensitive to the Au chain structure [7]. In addition, it is well known that the structure of the Si(557) and Si(775) surfaces change significantly, by faceting, both above and below the [5]).…”
Section: Copyright C Epla 2010mentioning
confidence: 95%
“…It has been shown previously, for the anisotropic systems, that the RAS response is very sensitive to the Au chain structure [7]. In addition, it is well known that the structure of the Si(557) and Si(775) surfaces change significantly, by faceting, both above and below the [5]).…”
Section: Copyright C Epla 2010mentioning
confidence: 95%
“…The computed RAS response of Si(557)-(5 Â 2)-Au is shown in Fig. 2(b) and compared with the available experimental data [12,38]. Like Si(111)-Au, the Si(557)-Au surface has been the subject of intensive study over the last decades, and as a result its structure is well known [2,39].…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 23 Augusmentioning
confidence: 99%
“…Recently, SXRD studies of Si(111)-5 × 2-Au, capped with 4.6 nm of amorphous Si (a-Si), showed that the positions of the Au atoms under the capping layer were essentially unchanged [18], raising the interesting possibility of successful capping of this nanowire structure with a-Si. However, RAS studies have shown that the anisotropic optical response of the (5 × 2)-Au structure is destroyed during capping, indicating that the technological interesting quasi-1D properties have been lost [19].…”
Section: Conventional Optical Techniques and Their Adaptationmentioning
confidence: 99%
“…• offcut Si(111) [19]. The conductivity of nanowires is a crucial parameter, but electrical contacting to such structures is a major problem, with the contacts often dominating the response of the system.…”
Section: Nanostructures and Solid-solid Interfacesmentioning
confidence: 99%